Penyuluhan Program “Gadis” (Gerakan Diet Seimbang) Di SMKN 3 Tahuna, Kepulauan Sangihe - Dhito Dwi Pramardika; Meityn Disye Kasaluhe; Wendy Alexander Tanod; Yana Sambeka; Destu Ayu Hasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Weight problems are often a concern for teenagers. Be it overweight or underweight. The GADIS (Balanced Diet Action) program counseling was carried out to increase knowledge about a healthy and balanced diet based on these problems. Including adolescents in the Sangihe Islands Regency, North Sulawesi Province, based on the results of dietary observations carried out, namely, eating one time a day to lose weight. The activity was conducted on February 11, 2022, at SMKN 3 Tahuna, Sangihe Islands Regency. Activities are carried out in counseling with lecture methods, discussions, and demonstrations. Sixty-nine students attended the training. The action results in the form of an increase in knowledge of 8.9 through the consequences of pre-test and post-test assessments. This activity aims to increase understanding about regulating the balance of nutrients through the type and portion of each person's needs.